Do metabolic syndrome and its components have an impact on bone mineral density in adolescents? - da Silva, Valéria Nóbrega (Nutr Metab (Lond), 2017)
In recent years, there has been growing concern about the occurrence of metabolic syndrome (MetS) at an early age and its effects on bone mass in adolescents. Adolescence is considered a critical period for bone mass gain. Impaired bone acquisition during this phase can lead to “suboptimal” peak bone mass and increase the risk of osteopenia/osteoporosis and fractures in old age. The objective of this review was to perform a critical analysis of articles that specifically focus on this age group, evaluating the influence of MetS and its components on bone mineral density in adolescents. A possible relationship between this syndrome and bone mass has been demonstrated, but the number of studies addressing this topic in adolescents is small. Despite the scarcity of evidence, the results of those studies show that Metabolic Syndrome is negatively correlated with bone mass and also that some components of MetS are negatively correlated with bone mineral density in adolescents. However, the associations between MetS and bone mass development need to be further explored in the age group corresponding to adolescence. Further good-quality studies are necessary to complement the understanding of this relationship.